Potensi Ekowisata Hutan Mangrove Di Desa Merak Belantung Kecamatan Kalianda Kabupaten Lampung Selatan - Sarwo Edy Saputra; Agus Setiawan (Jurnal Sylva Lestari, 2014)
Merak Belantung village in Kalianda sub district of South Lampung regency is a village located in coastal area. This village has a big ecotourism potential especially in its mangrove ecosystem. Despite of Merak Belantung tourism resource potentials, no research has been conducted to study aspects supporting this area into mangrove tourism development, so that data and information about this village is too general. A tourism development of a particular area needs a deep study from various aspects. The objectives of this research were to find out potentials and attractiveness of mangrove tourism in Merak Belantung village and to estimate the values of beauty from these potentials so that this area could be developed into tourism area supporting natural preservation and improving people welfare around it. This research was conducted from April to Desember 2013. Data were collected with direct observations in the fields and direct interviews with respondents to give assessment to tourism beauty potentials. Data were analyzed using descriptive method and scenic beauty estimation (SBE). The results showed that potentials and attraction of mangrove tourism object in Merak Belantung village was the mangrove ecosystem, mangrove water flow, river downstream and beach, local dance art, and handy craft. Activities could be conducted were photography, swimming, bird watching, canoeing, mangrove walk and fishing. Mangrove potential and tourism attraction in Merak Belantung village based on scenic beauty estimation (SBE) were high with the following SBE values: beach was 42, mangrove water flow was 20, and mangrove downstream was 19. Keywords: mangrove, tourism potential, merak belantung, scenic beauty estimation